Prognostic impact of baseline serum C‐reactive protein in patients with metastatic renal cell carcinoma (RCC) treated with sunitinib. (15th January 2014) - Beuselinck, Benoit; Vano, Yann‐Alexandre; Oudard, Stéphane; Wolter, Pascal; De Smet, Robert; Depoorter, Lore; Teghom, Corine; Karadimou, Alexandra; Zucman‐Rossi, Jessica; Debruyne, Philip R.; Van Poppel, Hendrik; Joniau, Steven; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of baseline serum C‐reactive protein (CRP) level on outcome in patients with metastatic renal cell carcinoma (mRCC) treated with sunitinib. Patients and Methods We reviewed the charts of patients with mRCC who started sunitinib as a first targeted treatment between 2005 and 2012 in three hospitals in Belgium and France. Collected data included known prognostic factors for mRCC, anatomical location of metastatic sites, response rate (RR), progression‐free survival (PFS) and overall survival (OS). Results A total of 200 eligible patients were identified by retrospective chart review. The median PFS and OS were 12 and 20 months, respectively. We observed a clear impact of baseline CRP levels on outcome: the median PFS was 25 months in the group with baseline CRP ≤5 mg/L and 8 months in the group with baseline CRP >5 mg/L (hazard ratio [HR] 2.48, 95% CI 1.74–3.59). The median OS in each group was 50 vs 12 months, respectively (HR 3.17, 2.20–4.68). In the group with baseline CRP ≤5 mg/L, 61% of patients experienced a partial response compared with 32% of patients in the group with baseline CRP >5 mg/L (difference = 29%, 95% CI 15–42). When adding baseline CRP (with a log transformation) to the six variables of the International Metastatic RCC Database Consortium (IMDC) model in a multivariable Cox regression model, baseline CRP was independently associated with poor PFS (HR for each doubling in CRP level: 1.14, 95% CI 1.03–1.26; P = 0.01) and OS (HR: 1.29, 95% CI 1.16–1.43; P < 0.001). Adding baseline CRP to the model increased the c‐statistic of PFS at 5 years from 0.63 (0.59–0.68) to 0.69 (0.65–0.73), and the c‐statistic of OS at 5 years from 0.65 (0.60–0.69) to 0.70 (0.66–0.74). Patients with elevated baseline CRP levels had a poor prognosis independent of the IMDC risk group, whereas patients with a low baseline CRP in the IMDC favourable risk group had a very good outcome. Conclusion Baseline serum CRP level is a strong independent variable linked with RR, PFS and OS in patients with mRCC treated with sunitinib.